51.3k views
0 votes
Help.help.help.pls.pls

Help.help.help.pls.pls-example-1

2 Answers

2 votes
-13y-5=8


Take 5 to the other side as a positive number


-13y=13


Divide both sides by -13


Therefore, y is equal to -1


But, the question isn't answered, we need to substitute the value of y into 4y+7, to fully answer the question



With our knowledge that y is equal to -1, the expression becomes



4*-1+7, which is 3


So, your answer is 3
User SEJU
by
5.4k points
5 votes

Answer: 3

========================================

Work Shown:

Solve the equation for y

-13y - 5 = 8

-13y = 8+5

-13y = 13

y = 13/(-13)

y = -1

Then use this y value to compute 4y+7

4y+7 = 4(-1)+7 = -4+7 = 3

User Pypyodbc
by
5.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.